A challenging review of childhood incontinence: rare complications of dysfunctional elimination syndrome in an epileptic boy - Aydoğdu, Ozgü; Burgu, Berk; Teber, Serap; Altugan, Semsa; Gökçe, Ilker; Deda, Gülhiz; Soygür, Tarkan (The Turkish Journal of Pediatrics, 2011)
A multidisciplinary approach is mandatory in defining the cause and directing the treatment of childhood urinary incontinence. Both pediatricians and pediatric urologists should carefully evaluate a child with incontinence for possible overlapping etiologies, before labeling him or her as a refractory case. We report an epileptic boy with dysfunctional elimination syndrome (DES) with associated rare complications of giggle incontinence and idiopathic urethritis, proving the need for a good voiding diary, patient history and structured symptom scores.